O formalnym opisie zjawisk ekonomicznych - Przybylska-Mazur, Agnieszka (About formal description of economic phenomena, 2011)
The formal description of economic phenomena requires the application of mathematical notions and mathematical techniques. When making formal description of economic phenomena we have to formulate all accepted assumptions in an open way. This prevents us from all errors and misunderstandings that can be created while formulating conclusions, results and forecasts. In this paper we present the advantages resulting from the application of formal description of economic phenomena. We also discuss approaches to the mathematical model link and we present some observations about the teaching of mathematics on economic studies
Didactics of Mathematics, 2011, Nr 8 (12), s. 119-126
Keywords: mathematical modelling; symbolic notation; mathematical economics; econometrics; teaching of mathematics